Application of response surface methodology to optimize the extraction of essential oil from Rosmarinus officinalis using microwave-assisted hydrodistillation - Majda Elyemni&, Bouchra Louaste, Faiçal El Ouadrhiri, Abdelhak Bouia, Noureddine Eloutassi (Journal of Applied Pharmaceutical Science, 2021)
The present study was conducted to optimize the microwave-assisted hydrodistillation process for the extraction of essential oils from Moroccan rosemary using response surface methodology. In this methodology, four independent variables were estimated by means of a central composite design in relation to essential oil yields, mainly extraction time (20, 55, and 90 minutes), microwave power (200, 400, and 600 W), water-to-plant ratio (2, 4, and 6 ml/g), and drying period (0, 7, and 14 days). The extraction yield according to the mathematical regression model correlation analysis was expressed using a second-order polynomial. The maximum essential oils’ yield was found to be 1.326% at the optimum conditions of 20 minutes, 600 W, 2 ml/g, and 7 days.
Keywords: Rosmarinus officinalis, essential oil, response surface methodology, and microwave-assisted hydrodistillation.